Bioaccumulation of potentially toxic elements in fish species from aquatic environments located in crowded areas of southern Romania - P Ionescu; V M Radu; Gy Deak; I E Ciobotaru; E Marcu; E Diacu; M Pipirigeanu (Technium: Romanian Journal of Applied Sciences and Technology, 2019)
Taking into consideration that fish are valuable bioindicators for assessing pollution with potentially toxic elements (PTEs) such as heavy metals from aquatic environments, this study aimed to assess bioaccumulation factors in relation to water (BAF) and sediment (BASF) for the following potential toxic elements: Cd, Pb, Hg, Cu, Cr, Ni and Zn from 6 different fish species (Alburnus alburnus, Carassius gibelio, Scardinius erythrophthalmus, Ameiurus nebulosus, Perca fluviatilis, Lepomis gibbosus). Fish species have been captured from the waters of the Arges River (Hotarele village area) and the Colentina River (particularly from Mogosoaia, Herastrau and Panteliom lakes), from crowded areas located in the southern part of Romania. The results of the analysis indicated BAF values > 1 for the most fish species captured from the Colentina River. BASF values > 1 were obtained for BASFPb (Carassius gibelio - Arges River), BASFNi (Scardinius erythrophthalmus - Herastaru L. and Perca fluviatillis - Pantelimon L.), BASFCr (Perca fluviatillis - Pantelimon L.) and BASFZn (Alburnus alburnus and Scardinius erythrophthalmus - Mogosoaia L. and Carassius gibelio - Pantelimon L.). The obtained results can be used to describe the transfer of these elements from water and sediments to the fish tissue.